PERSEPSI PETANI PADI SAWAH TERHADAP POLA KEMITRAAN DENGAN BADAN USAHA MILIK RAKYAT (BUMR) PANGAN - Riantin Hikmah Widi; Tuti Karyani; Hepi Hapsari; Lucyana Trimo; Tedi Hartoyo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Society-owned enterprises (BUMR) Food offer partnership patterns with farmers to overcome the classic problems faced by farmers so far, namely the low capital, access to sources of capital, access to technology, and market penetration. The partnership pattern offered by BUMR Food is in the form of non-collateral loan assistance accompanied by assistance and providing agricultural insurance to farmers. Farmers are required to plant rice using varieties determined by the BUMR Food and sell their grain to BUMR Food at a price determined based on the quality of grain produced by farmers. Farmers' decision to establish a partnership with BUMR Food is greatly influenced by their perception of the partnership pattern. The purpose of this study is to: (1) identify the pattern of partnership of paddy rice farmers with BUMR Food, and (2) analyze the perception of paddy rice farmers to the pattern of partnership with BUMR Food. The research method used was a survey, with a population of all paddy rice farmers who followed the pattern of collaboration with the BUMR Food in Sukabumi Regency. The sampling technique used is Simple Random Sampling. The first research objective was analyzed descriptively, while the second research objective was analyzed using the Spearman Rank correlation test. The results show: (1) The partnership pattern in the form of Agribusiness Operational Cooperation, where the partner company (BUMR Food) provides non-collateral loans, provides technical assistance in cultivation, and acts as an offtaker (receives the results of production), and (2) the perception of farmers lowland rice to the partnership pattern with BUMR Food is generally positive both in terms of relative profitability, suitability and complexity.